2016
DOI: 10.1002/cncr.30022
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization syndrome: New insights in psychosocial cancer care

Abstract: The psychological reactions of patients in response to cancer have been the object of psycho-oncology research since the first studies carried out by Arthur M. Sutherland in the middle of the last century.1 Subsequent better designed investigations were carried out in many parts of the world using standardized psychiatric interviews according to the Diagnostic Statistical Manual for Mental Disorders (DSM) of the American Psychiatric Association and the International Classification of Diseases (ICD) of the Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 33 publications
6
41
0
3
Order By: Relevance
“…These results are comparable to those of Grassi et al, 36 who found combined diagnoses of depression and demoralization in 6% of patients with breast and gastrointestinal cancer, with 23% being demoralized but not depressed. 37 Demoralization was significantly associated with suicidal ideation in this study. 22,23,31 A similar rate of 19% was found with a revised version of the DS.…”
Section: Discussionsupporting
confidence: 50%
“…These results are comparable to those of Grassi et al, 36 who found combined diagnoses of depression and demoralization in 6% of patients with breast and gastrointestinal cancer, with 23% being demoralized but not depressed. 37 Demoralization was significantly associated with suicidal ideation in this study. 22,23,31 A similar rate of 19% was found with a revised version of the DS.…”
Section: Discussionsupporting
confidence: 50%
“…mindfulness-based and contemplative practices) have been translated into a (secular) set of behavioral skills and successfully implemented in dialectic behavior therapy (DBT) for suicidal patients (Linehan and Wilks 2015;Baumann 2016). Also, similar to PTSD patients, palliative care patients faced with a life-threatening, incurable illness often suffer from demoralization, that is, a feeling of hopelessness due to a loss of their sense of meaning in life (Grassi & Nanni 2016). One approach that has been developed for use in palliative care patients is Dignity Therapy (Chochinov 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of prospective evaluation was underlined in a recent, large, prospective German study, which reported a 31.8% prevalence of mental disorders 4 weeks after diagnosis and a 39.8% prevalence at 12 months using the same instrument we used (CIDI). Finally, although we used a formal, semistructured psychiatric interview as a current gold standard to make diagnoses according to the ICD‐10, it is possible that subthreshold disturbances or other clinical expressions of significantly maladaptive responses to cancer (eg, demoralization, abnormal illness behavior) may have gone unrecognized. These psychological reactions often are not picked up by classic psychiatric nosological systems but could affect from 15% to 20% of patients with cancer …”
Section: Discussionmentioning
confidence: 99%